2013
DOI: 10.3389/fnhum.2013.00691
|View full text |Cite
|
Sign up to set email alerts
|

Maturational delay in ADHD: evidence from CPT

Abstract: While data from behavioral, neuropsychological, and brain studies suggested that Attention-Deficit/Hyperactivity Disorder (ADHD) is related to a developmental lag that reduces with age, other studies have proposed that ADHD represents a deviant brain function. The present study used a cross-sectional approach to examine whether ADHD children show a developmental delay in cognitive performance measured by continuous performance test (CPT). We thus, compared six age groups of ADHD children (N = 559) and their un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
37
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 57 publications
8
37
1
2
Order By: Relevance
“…At baseline, height SDS and weight SDS z scores were higher than expected in our study which is not coherent with the studies suggesting that patients with ADHD show physical growth delay intrinsic to the disorder [15,16]. According to the "maturational delay" in ADHD, a delay in prefrontal cortical regions has been described [17,18] if the same condition was not associated with an intrinsic delay of physical development. Our results are coherent with other studies which compared the prevalence of higher body weight or body mass index in children and adolescents with ADHD [19,20].…”
Section: Discussioncontrasting
confidence: 95%
“…At baseline, height SDS and weight SDS z scores were higher than expected in our study which is not coherent with the studies suggesting that patients with ADHD show physical growth delay intrinsic to the disorder [15,16]. According to the "maturational delay" in ADHD, a delay in prefrontal cortical regions has been described [17,18] if the same condition was not associated with an intrinsic delay of physical development. Our results are coherent with other studies which compared the prevalence of higher body weight or body mass index in children and adolescents with ADHD [19,20].…”
Section: Discussioncontrasting
confidence: 95%
“…Another limitation of the study is our inability to study gender differences separately for children and adolescents due to our limited sample size. Indices of CPT performance, including the level of distractibility, were previously associated with age (Berger et al, 2013;Slobodin et al, 2015). Therefore, it will be worthwhile to study gender effects on developmental trajectories of ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Children with ADHD or ASD exhibit inferior inhibitory control compared to healthy control children 42,43) . A developmental cross-sectional study indicated that children with ADHD exhibit delayed development of executive function compared to typically developing children 44) . Furthermore, relative to typical developed children, children with ADHD, ASD, and dyslexia have abnormal brain structure [45][46][47] , and exhibit differential brain activation during the resting state 48) , as well as during executive function tasks [49][50][51] .…”
Section: Neurodevelopmental Disorders and Executive Functionmentioning
confidence: 99%